in a good way: (Re)grounding Contextual Narratives on Turtle Island - Lalor, Amina (University of Waterloo, 2020)
Canada is a settler-colonial nation built on Indigenous lands. Architecture in this context is not a neutral practice. Together with urban planning, it has played a key role in the genocidal dispossession, displacement, and assimilation of Indigenous peoples by imposing private property, Euro-Western settlement, and exploitative land development. The architectural industry across Turtle Island (North America) unfolds within discriminatory, imperialist, and capitalist power structures. It remains complicit in ongoing colonial violence towards Indigenous peoples, and the land upon which we all depend. This thesis documents the process of unsettling and (re)grounding the contextual narratives that frame my work as a Métis-Irish-Vietnamese designer in Southern Ontario on the ancestral lands of the Chonnonton (Neutral/Attawandaron), the Anishinaabeg (Ojibwe/Mississaugas), and the Haudenosaunee (Six Nations/Iroquois) peoples. Within this work I broaden the concept of an architectural “site analysis” to include a deeper context of settler colonialism, Indigenous resistance, and the experiences I carry with me as a designer and a human being. How do we, as architects, reconcile our practice within a settler-colonial context violently inscribed onto Indigenous lands? How do we confront our complicity in Indigenous erasure and honour the treaties and kinship networks that underlie our presence on this ground? Amid an escalating climate crisis, and acknowledging architecture as a land-based practice, how do we mend our relationships with the land, water, plants, and animals? Through reflections, essays, photographs, and illustrations, I map the journey of recalibrating my own relationships to place, in search of what it means to design and build in "a good way."